If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3x + 6) = 84 Reorder the terms: 4(6 + 3x) = 84 (6 * 4 + 3x * 4) = 84 (24 + 12x) = 84 Solving 24 + 12x = 84 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + 12x = 84 + -24 Combine like terms: 24 + -24 = 0 0 + 12x = 84 + -24 12x = 84 + -24 Combine like terms: 84 + -24 = 60 12x = 60 Divide each side by '12'. x = 5 Simplifying x = 5
| 153=9x+5 | | 24-2x=20 | | 005(12-3y)-9x=4(3-2x) | | 2x+10=4x+54 | | 5x-1=8x-4 | | 4(6x+8)=56 | | m=n+14 | | 3x+x+2=4 | | 6+5w+2w=13 | | 2.25x+2=12 | | 2a+13-a=10 | | (x-10)=3 | | 4x-7+1y-7x-[-3y]= | | -10+x+4=7x | | -1x+8+6x-4y-8x+3= | | 12x=8x-4 | | (x)+1=7 | | abs(3-6x)=10 | | 3x(5x-6)= | | 4567r-(56+7895)=-6754 | | 41-u=22 | | 3/4*2=y | | w+9w= | | x+(x*.08)=4900 | | 16=4k | | 3(2x-5)=4x+7 | | 1.2z+1.152=30.6 | | 4(x-7)(x-8)(x+7)=0 | | 12+3y-8+4y= | | 0.5x+5.4=8.6 | | 0=x^2+0-67 | | -3(x-3)=21 |